Implementation of Comprehensive Guidance and Counseling Program in Schools - Hasibuan, Ummi Kalsum; Ahmad, Riska; Syukur, Yarmis (Universitas Trunojoyo Madura, 2023)
Comprehensive guidance and counseling is an actual perspective that focuses on positive assumptions about human potential. Based on these assumptions Bk considers it as a facility for students for their development. After all this time Bk has always been seen only as a solver and healer of counselee problems. However, there are other functions such as prevention, education, and development. Therefore the application of comprehensive counseling requires the support of a full understanding of developmental counseling. The service programs are basic services, responsive services, individual planning system support. Comprehensive Bk implementation activity is supported by various related parties. Raise awareness of student development that requires maximum cooperation from various parties. In this study, the counselor or Bk teacher has a large enough role to run the program by having a proportional amount of guidance time, namely 80% which is directive to students. Meanwhile, in program management activities and system support, the time is 20%.